A Rare Cause of Colon Perforation; Intrauterin Device - Onur Olgaç Karagülle; Erkan Yavuz; Hüseyin Bilge; Barış Sana; Aydın Zilan; Fatih Çelebi (İstanbul Medical Journal, 2019)

(untitled)
Intrauterin device (IUD) is one of the most common used contraseptive methods in the world. Migration of IUD to sigmoid colon is a rare and serious complication. This report represents a case with an acute abdominal condition due to a migrating IUD which perforated the uterus and migrated to and perforated the sigmoid colon. IUD was removed from the abdomen laparoscopically and at the same session, laparoscopic repair of the sigmoid colon and uterus were performed. Laparoscopy is a reliable method for patients with lost intra-abdominal IUD which migrates by perforating the uterus. It enables repair of organ perforations at the same session and provides less tissue damage by minimal incision, less postoperative pain and decreased risk of intra-abdominal adhesion and therefore, facilitating the patient’s comfort and decreasing duration of hospitalization.